إستخدامات تلاميذ الثانوية لمواقع التواصل الإجتماعي التيك توك نموذجا والإشباعات المحققة منه - خادم الله، خديجة, قماري، رومايصاء (جامعة الوادي university of Eloued, 2020)
Abstract: This study came under the title of the impact of high school students 'use of the TikTok application, and the problem of the study centered on the motives of high school students' use of the TikTok website and application by answering the following questions: _ What are the habits and patterns of using the TikTok website and application by high school students? _ What are the purposes of high school students in using the TikTok website and application? _Did high school students choose the TikTok website and application? _ What are the gratifications that high school students achieve from using the TikTok website and application? The study aimed at the following: Knowing the habits and patterns of high school students' use of social media. _ Know as well as the habits and patterns of using high school students to the site and application of TikTok. _ A disclosure of the achievements achieved by high school students' use of the TikTok website and application This study was conducted on 55 samples from the secondary school students of Abdul Aziz Al-Sharif in the state of Al-Wadi, and in this endeavor we used the survey method, which was determined by the method of the intentional sample. Secondary pupils for social media, the third axis is the habits and patterns of high school students ’use of the tiktok site, the fourth axis was the motives for high school students’ use of the tiktok site, and finally the fifth axis contained the gratifications achieved from high school students ’use of tiktok. The study summarized a set of results, the most important of which was that females use social networks more than males, while the most used age group is between 17-18 years, which is the most common category compared to others, and the hourly volume they spend on the teak app is less than an hour motivated by playing, entertaining and chatting to get rid of Boredom and moving away from the daily routine, and the application of TikTok does not meet the needs of students without resorting to other sites and they benefit from it to a very small degree. From here we conclude that the TikTok site is not one of the students' priorities in using and being exposed to it, meaning that there are other sites that took their attention and time and achieved more satisfaction for them as a result of their use of them.
دراسة ميدانية لعينة من تلاميذ ثانوية عبد العزيز الشريف الوادي
مذكرة ماستر إعلام تخصص سمعي بصري
Keywords: مواقع التواصل الإجتماعي، التيك توك; Sites de réseautage social, tik tok; Social networking sites, tik tok